Effect of melanism of alpine Colias nastes butterflies (Lepidoptera: Pieridae) on activity and predation ... - Roland, J. (University of Alberta Library, 2006)
Abstract: Melanism in the Sulphur butterfly Colias nastes Boisduval was quantified and related to their ability to remain active under cool or cloudy conditions and to their risk of predation. Darker individuals were more active, moved greater distances, and disappeared from the population at a greater rate. Disappearance of darker individuals was not due to greater predation. Light-coloured individuals suffered greater predation than dark individuals, but only at higher elevations. The broad geographical pattern of increased melanism in Arctic and alpine Colias butterflies is likely a response to the consistent pattern of cooler temperatures in these habitats rather than local variation in predation pressure. ...